2014
DOI: 10.1208/s12249-014-0134-7
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Granules Produced by High-Shear and Fluidized-Bed Granulation Methods

Abstract: Abstract. Placebo granules were manufactured by both wet high-shear and fluidized-bed techniques. The granules were compared based on size, shape, surface morphology, and a variety of different flowability measurements. This comparison showed that granule formation and growth were different, with induction growth for high-shear granulation and steady growth for fluidized-bed granulation. Final granules from high-shear granulation were more spherical and dense compared with the irregular granules from fluidized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…Circularity generally depends on the method of granulation. 21) Our results were similar to those obtained with granules produced by rotary granulation, which indicated that the mechanism of granulation in our study was rotation of granules in the vessel.…”
Section: Available Water Content Range For 20% Ibp Granulessupporting
confidence: 90%
See 1 more Smart Citation
“…Circularity generally depends on the method of granulation. 21) Our results were similar to those obtained with granules produced by rotary granulation, which indicated that the mechanism of granulation in our study was rotation of granules in the vessel.…”
Section: Available Water Content Range For 20% Ibp Granulessupporting
confidence: 90%
“…In previous studies that determined PL values, a wet mass was produced using a mortar and pestle, and then rolled into a rod by hand. 20) In the present method, a wet mass was produced in a closed vessel using a mixer, and force measurements were acquired within in a few seconds using a digital gauge.…”
Section: Resultsmentioning
confidence: 99%
“…-3 -more irregular shape than those produced by using rotating drums and mechanical shear mixer (Jacob, 2007;Ji, Fitzpatrick, Cronin, Fenelon, & Miao, 2017;Morin & Briens, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In fluid bed granulators, the powder bed is first fluidized by a flow of air injected upward through a distributor plate at the base of the granulator, and then the liquid binder is sprayed through a nozzle onto the fluidized bed to agglomerate powder in granules. When binder spraying is stopped, the granules continue to dry in the fluidizing airstream, avoiding the use of a following drying step [18]. This type of granulator is flexible, relatively easy to scale, difficult for cohesive powders, and good for coating applications [16].…”
Section: Wet Granulation Process: Apparatus and Process Parameters 2mentioning
confidence: 99%